“A Journal of Health for All the Estates” by Franz Leopold Lafontaine and the Standard of Medical Knowledge in the Early 19th Century. Selected Diseases - Polak, Szymon (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The issue of diseases and attempts to treat them has troubled humanity since the dawn of time. However, with the passage of time, the state of medical knowledge grew, and in the Renaissance there was a real revival of human sciences, which resulted in the works of such people as Andreas Vesalius, William Harvey or Giambattista Morgagni, and in the Commonwealth Wojciech Oczko or Joachim Delhafius. The symbolic work that introduces medicine not only in the nineteenth century, but also into the deep province is the „Health Journal for All States” by Franz Leopold Lafontaine. The analysis of three types of diseases: tuberculosis, smug and dental issues in relation to other researchers allows to compare the state of medical knowledge not only with what occurred before, but also with how these diseases were later looked at.